The value of work in the perspective of prospective and active teachers - Joanna M. Łukasik (Institute of Social Affairs of the Pedagogical University of Cracow, 2023)
The paper focuses on the value of work from the point of view of prospective and active teachers. Referring to the emancipatory and axiological understanding of the categories of work and value of work, a study in the qualitative paradigm was conducted among 196 teachers and candidates to become teachers. The method of text analysis of essays and diaries was used to answer the following research question: What values are assigned to work by prospective and professionally active teachers? The research material was analysed regarding the category of work as understood by W. Dróżka. The purpose of it was to show similarities and differences in the values assigned to work by different age groups and students at different stages of teacher training and active teachers. These values were generated by certain professional experience or image of the work. The conclusions focus on practical solutions that may be applied to teacher education. Keywords: teacher, work, value of work Wartość pracy w perspektywie kandydatów do zawodu oraz nauczycieli W artykule skoncentrowano się na wartości pracy w ujęciu kandydatów do zawodu nauczyciela oraz nauczycieli czynnych zawodowo. Odnosząc się do emancypacyjnego i aksjologicznego rozumienia kategorii praca oraz wartość pracy przeprowadzono badania z w paradygmacie jakościowym wśród 196 nauczycieli i kandydatów do zawodu. W artykule wykorzystano metodę analizy treści esejów oraz materiałów pamiętnikarskich w celu uzyskania odpowiedzi na pytanie badawcze: Jakie wartości nadają pracy kandydaci do zawodu i czynni zawodowo nauczyciele? Materiał badawczy przeanalizowano w perspektywie kategorii wartości pracy w ujęciu W. Dróżki dla ukazania określeń i znaczeń różnych grup wiekowych oraz osób na różnych etapach kształcenia do zawodu nauczyciela i czynnych zawodowo w kontekście uchwycenia podobieństw i różnic przypisywanych pracy wartościach, generowanych określonym doświadczeniem zawodowym lub wyobrażeniem o pracy. We wnioskach końcowych wskazano aplikacje do praktyki w zakresie edukacji nauczycieli.